An Integrated Model of Athletes' PED Use: A Test of Low Self-Control, Opportunity, Deviant Peer Associations, and Control Deficit. Issue 10 (3rd October 2021) - Kabiri, Saeed; Masoomeh (Shamila) Shadmanfaat, Seyyedeh; Donner, Christopher M.; Cochran, John K.
ABSTRACT: The use of performance-enhancing drugs (PED) in sports is an important social issue. This is particularly true given the recent high-profile doping incidents from a multitude of professional athletic competitions around the world. Because of the numerous individual, team, and socio-political consequences that can stem from sports doping, it has become vital to explore the etiology of PED use among athletes. As such, Gottfredson and Hirschi's general theory of crime is one theory that may help explain this deviant behavior. Using an integrated theoretical model, the purpose of this study was to examine the influence of low self-control, opportunity, deviant peers, and control deficit on professional athletes' use of PEDs. Survey data from 709 professional athletes in Iran was collected and analyzed. Structural equation modeling demonstrated that all of the theoretical variables had direct and significant effects on PED use. Specific findings, policy implications, and study limitations are discussed.